The Impact of Audit Quality, Auditor Reputation, and Auditor Rotation on the Market Value of Companies on the Indonesia Stock Exchange - Loso Judijanto; Deni Iskandar (Westscience Press, 2024)
This study investigates the effects of audit quality, auditor reputation, and auditor rotation on the market value of companies listed on the Indonesia Stock Exchange. Using a quantitative approach, the research analyzed data from 150 companies, collected through structured questionnaires and audited financial reports. The relationships among variables were tested using Structural Equation Modeling-Partial Least Squares (SEM-PLS 3). The results show that audit quality, auditor reputation, and auditor rotation significantly and positively influence market value, with audit quality having the strongest effect. These findings highlight the critical role of robust auditing practices in enhancing investor confidence and corporate valuation. Practical recommendations for companies, auditors, and regulators are provided to strengthen the financial reporting ecosystem and ensure sustainable market growth.